3(r+1.6)-8r=9.5

Simplify each term.

Apply the distributive property.

3r+3⋅1.6-8r=9.5

Multiply 3 by 1.6.

3r+4.8-8r=9.5

3r+4.8-8r=9.5

Subtract 8r from 3r.

-5r+4.8=9.5

-5r+4.8=9.5

Subtract 4.8 from both sides of the equation.

-5r=9.5-4.8

Subtract 4.8 from 9.5.

-5r=4.7

-5r=4.7

Divide each term in -5r=4.7 by -5.

-5r-5=4.7-5

Cancel the common factor of -5.

Cancel the common factor.

-5r-5=4.7-5

Divide r by 1.

r=4.7-5

r=4.7-5

Divide 4.7 by -5.

r=-0.94

r=-0.94

Solve for r 3(r+1.6)-8r=9.5